Reflection of Emotions in the Poems of the Poet ( Badrakhan Al-Sindi) - Ahmed, Dawlat; Taher, Nizar (Humanities Journal of University of Zakho, 2021)
This study tries to show the extent and manner of emotional embodiment in the poetic text. As it is known, emotions are considered as one of the main elements in the literary text in general and in the poetic text in particular, and they carry a broad meaning of the literary text within them. The study entitled (Reflection of Emotions in the Poems of the Poet ( Badrakhan Al-Sindi) was divided into two parts. The first part was devoted to the theoretical aspect of the study in which we discussed the relationship between literature and psychology along with the concept and what emotions are in the poetic text. The second part highlighted practical aspect of the study. Several poems of the aforementioned poet were analyzed in terms of emotions, and in the end, it became clear to us that the multiplicity of emotions is a major feature of the poems, as well as they include two main types of emotions. Moreover, they embody an intense emotion through which we concluded that these poems contain a highly sensitive emotion.